2022
DOI: 10.18502/ijrm.v20i5.11049
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperbaric oxygen therapy in the inflammatory response in a mouse model of endometriosis: An experimental study

Abstract: Background: Endometriosis pathogenesis is related to the inflammation shown by the secretion of pro-inflammatory mediators. This hypoxia condition can stimulate this condition. Objective: To investigate the effect of hyperbaric oxygen therapy (HBOT) on the inflammation reaction of endometriosis-induced mice. Materials and Methods: The animals were designated into 3 groups: I) the pre-test group, II) the post-test group receiving the HBOT, and III) the post-test group without HBOT. All groups were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Conversely, when HBO 2 treatment is administered in hypoxic conditions with a derivational elevated HIF-1α, HBO 2 treatment decreased the disease-mediated high levels of HIF-1α [ 61 , 119 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. The evaluation of studies performed in conditions of relative hypoxia secondary to inflammation indicates that the effect of HBO 2 on HIF-1α protein expression is dependent on the number of HBO 2 sessions administered, with HBO 2 having an increasing effect when administered in up to five sessions [ 140 , 141 , 142 , 143 ], and treatment with more than six sessions having a decreasing effect under these conditions [ 47 , 120 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. However, six study results were not supportive of this trend [ 117 , 140 , 141 , 157 , 158 , 159 ].…”
Section: Tolerance To Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when HBO 2 treatment is administered in hypoxic conditions with a derivational elevated HIF-1α, HBO 2 treatment decreased the disease-mediated high levels of HIF-1α [ 61 , 119 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. The evaluation of studies performed in conditions of relative hypoxia secondary to inflammation indicates that the effect of HBO 2 on HIF-1α protein expression is dependent on the number of HBO 2 sessions administered, with HBO 2 having an increasing effect when administered in up to five sessions [ 140 , 141 , 142 , 143 ], and treatment with more than six sessions having a decreasing effect under these conditions [ 47 , 120 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. However, six study results were not supportive of this trend [ 117 , 140 , 141 , 157 , 158 , 159 ].…”
Section: Tolerance To Infectionmentioning
confidence: 99%
“…Studies looking at the impact of HBO 2 on the expression on NF-κB similarly found an increasing effect in a normoxic environment [ 17 , 117 , 160 ] and a decreasing effect in a hypoxic environment [ 161 , 162 ], regardless of the stage of inflammation. In contrast to HIF-1α expression, studies evaluating the effect on NF-κB signaling in conditions of relative hypoxia secondary to inflammatory conditions mostly found a decreasing effect regardless of the inflammatory state or number of HBO 2 sessions [ 46 , 47 , 153 , 154 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ], with the exception of three studies where 10–30 sessions of HBO 2 were applied to chronic inflammation, which found an increasing effect [ 117 ] or no effect (Part b in Table 1 ) [ 149 , 158 ].…”
Section: Tolerance To Infectionmentioning
confidence: 99%